Pengaruh Perendaman Nilon Termoplastik Dalam Berbagai Konsentrasi Ekstrak Bunga Cengkeh Terhadap Modulus Elastisitas (The Effect of Thermoplastic Nylon Immersion In Various Concentration of Clove Flower Extract to the Modulus Elasticity) - Rachel Priskila Louwrensya Warinussy; Dewi Kristiana; FX Ady Soesetijo (Pustaka Kesehatan, 2018)
Background:Thermoplastic nylon is one of denture basic alternative made by resin polyamide because its high flexibility and good translutient, but hard to be smoothed and polished causing food waste accumulation and plaque formation. Clove flower extract proved as antiseptic used to be a denture cleanser material, but its contens of phenol essence can break the thermoplastic nylon chain. Purpose: The aim of this study was to determine the effect of thermoplastic nylon immersion in various concentration: 0,8%, 1%, 1,2%, 1,4% and 1,6%, of clove flower extract to the modulus elasticity. Materials and Methods: This study was an laboratories experimental using post-test only control group design. The samples in 65 mm x 10 mm x 2,5 mm size were 30 samples. Those samples grouped into 6 groups immersed in aquadest and clove flower extract solution that is grouped based on the concentrations: 0,8%, 1%, 1,2%, 1,4% and 1,6% for 23 days. The modulus elasticity of thermoplastic nylon measured with Universal Testing Machine (UTM). Data was analysed using One Way Anova. Result and Conclusions: the conclusion of this study represented that thermoplastic nylon plates immersion in clove flower extract at the concentration 0,8%, 1%, 1,2%, 1,4% and 1,6% was affected the modulus elasticitys. The most effective clove extract concentration to be use as denture cleanser was 1,6% because it has the lowest increasing value of nylon thermoplastic modulus elasticity. Keyword: Clove flower extract, modulus elasticity, thermoplastic nylon.